2010
DOI: 10.1038/jhh.2010.64
|View full text |Cite
|
Sign up to set email alerts
|

How early should blood pressure control be achieved for optimal cardiovascular outcomes?

Abstract: As a consequence of the aging population and the increasing prevalence rates for conditions such as type 2 diabetes and chronic kidney disease (CKD), management of hypertension will be focusing more and more on the high-risk patient. Clinical practice guidelines for managing hypertension in the United States recommend a target blood pressure (BP) o130/80 mm Hg in patients with diabetes or CKD, notably lower than the 140/90-mm Hg threshold for the general hypertensive population. However, the optimal timeframe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…While these trials were not designed to investigate speed of BP lowering or time to BP goal, there would appear to be some correlation between BP reduction within a certain time frame (1–6 months) and CV outcomes. It has also been suggested that early control of BP may impart a physiological memory that results in outcomes benefits over the long term . This is supported by the results of the Aliskiren and the Calcium Channel Blocker Amlodipine Combination as an Initial Treatment Strategy for Hypertension (ACCELERATE) trial.…”
Section: Discussionmentioning
confidence: 94%
“…While these trials were not designed to investigate speed of BP lowering or time to BP goal, there would appear to be some correlation between BP reduction within a certain time frame (1–6 months) and CV outcomes. It has also been suggested that early control of BP may impart a physiological memory that results in outcomes benefits over the long term . This is supported by the results of the Aliskiren and the Calcium Channel Blocker Amlodipine Combination as an Initial Treatment Strategy for Hypertension (ACCELERATE) trial.…”
Section: Discussionmentioning
confidence: 94%
“…Fast and sustained blood pressure (BP) control in the management of hypertension is paramount [1,2]. To achieve this objective, many guidelines recommend initial combination therapy, as this approach has advantages related to compliance, efficacy and safety [35].…”
Section: Introductionmentioning
confidence: 99%
“…This has been associated with improved outcomes in studies of high-risk patients. 26 The mechanism of BP lowering is likely to be a combination of changes in prescriptions of lifestyle and medications as well as changes in adherence to therapy. 27 The use of the hypertension flow sheet may have contributed to the improved documentation and potentially improved assessment of medication therapy as well as a patient-selected lifestyle goal as the flow sheet included a field to document a patient-selected lifestyle goal.…”
Section: Discussionmentioning
confidence: 99%